Learners’ access to tools and experience with technology at the University of the South Pacific: Readiness for e-learning - Raturi, Shikha; Hogan, Robert; Thaman, Konai Helu (Australasian Journal of Educational Technology, 2011)
Technology in higher education has become exceedingly popular and useful; however, a digital divide generally applies to the use of technology in education in many developing countries. The Pacific Island countries differ in their technological capacities and infrastructure, with the Fijian capital Suva being most technologically and infrastructurally advanced compared with other towns in Fiji and in other Pacific Island countries. This led the researchers to investigate access to e-learning tools and experience with technology amongst a group of 92 students, ranging from 18 to over 55 years of age, enrolled in postgraduate courses in education at the University of the South Pacific. A survey consisting of questions on age, gender, qualification, professional experience, ethnicity and access to and experience with technology was carried out for one cohort. The findings indicate an encouraging level of readiness for e-learning.